Effect of Shape and Slenderness Ratio on the Behavior of Laterally Loaded Piles - Abbas, Jasim M.; Mohammed Shafiqu, Qassun S.; Taha, Mohd R. (Nahrain University College of Engineering Journal, 2008)
In case of piles subjected to lateral loading, the failure mechanisms of short pile under lateral loads are different from that of long pile case. The lateral load capacity of pile is limited in lateral deformation of the pile that effected directly on the contact surface area. The results of the 3D finite element analysis for the problem of a single pile under lateral loadings are presented in this paper. The effect of pile shape for both circular and square crosssection on pile response was investigated. Also the influence of slenderness ratio L/B on the pile deformation was discussed in this study. Linear elastic model was used for modeling the piles. Mohr-Coulomb model was used to simulate the surrounded soil. The pile soil interaction composed of 16-node interface elements. A good correlation between the experiments and the analysis was observed in validation example. It was found that the pile response is affected by the amount of loading, the pile cross sectional shape and pile slenderness ratio. The lateral resisting of pile increase in proportioned to the square shape of the pile. In both pile shape, a short pile (L/B = 8.3) gave a small amount of lateral tip deflection than the long pile with a slenderness ratio more than 8.3 for the same amount of loading. Also, the negative base deflection is high for short pile and reduces to zero for long pile.